Lichenoid drug eruption induced by rosuvastatin, a case report and review literatures (Eng) - Norasetthada, Angkana (Thai Journal of Rheumatology, 2025)
Cutaneous drug reactions have a wide variety of clinical features. Lichenoid drug eruptions (LDE) are rare and it may be difficult to differentiate them from idiopathic lichen planus. Gold, quinine, quinidine and penicillamine are well-known inducers of such eruptions1,2, but there are only a few reports of lichenoid eruption induced by 3-hydroxy-3-methyl-glutaryl coenzyme A (HMG-CoA) reductase inhibitors (statin)2,3. I described a lichenoid eruption linked to atorvastatin and rosuvastatin. His clinical features, in addition to histological findings, helped to establish the diagnosis. The cutaneous eruption resolved one month after the cessation of rosuvastatin. and a proposed alternative regimen to reduce total cholesterol (TC) and LDL-C in a patient with atherosclerotic heart disease. For this case study, the patient gave written informed consent.